Management of Temporo-Mandibular Disorders in children and adolescents: A literature review - Rosales ME, Miguel; Garrocho DC, José; Ruiz MC, María; Márquez MC, Raúl; Pozos PhD, Amaury (Odovtos - International Journal of Dental Sciences, 2016)
The purpose of this review is to provide the fundamental information for the early diagnosis of temporomandibular disorders (TMD) in children and adolescents, taking in account that the general trend among Dentists is to believe that these kind of disorders do not occur in the pediatric patient, or that they are present very rarely. However, this is not true; therefore, it is mandatory that, during the comprehensive clinical exam of the pediatric patient, a meticulous evaluation of the developing temporomandibular joint is included. The present paper pretends to serve as encourage interested to general and specialist Dentists on this important issue, and capable to advise, guide or treat their own patients, particularly young children; these patients cannot often communicate sufficiently their symptoms, because of their immaturity. Thus, only through a full exam, temporomandibular disturbances can be properly assessed, diagnosed and treated.